Evaluation the Levels of Melatonin, Glutathione Peroxidase and Superoxide Dismutase Enzymes in Prediabetic Individuals - Zeena Abd Ali (The Iraqi Journal of Medical Sciences)
Background: Prediabetes is a serious health condition where blood sugar levels are higher than normal, but not high enough yet to be diagnosed as type 2 diabetes. Diabetes mellitus (DM) is a disease characterized by elevated blood glucose levels due to the inability of the body to yield or use insulin or both. It is believed that oxidative stress may play an important role in the development of vascular complications in patients with type 2 diabetes mellitus. Objective: To evaluate the serum levels of endogenous melatonin and its association with superoxide dismutase (SOD) and glutathione peroxidase (GPx) in prediabetes individuals in comparison with normal individuals as controls. Methods: Endogenous melatonin and SOD concentrations were measured in sera of 50 prediabetes individuals in comparison with 50 volunteers enlisted as normal controls aged from 20 to 65 using enzyme-linked immunosorbent assay (ELISA); volunteers enlisted as normal. Serum levels of lipid profile, urea, creatinine, GPx, fasting blood glucose and plasma level of glycated hemoglobin (HbA1c) were measured. All individuals were matched for body mass index and sex. Results: Serum levels of melatonin, SOD and GPx enzymes in prediabetic patients were significantly lower than those of controls (p=0.036, p=0.024, and p=0.044; respectively) in prediabetic individuals when compared with controls with a significant positive correlation of theses biomarker levels in prediabetic individuals as compared with the control group. Conclusion: Decreased levels of melatonin in prediabetic subjects may play an essential role by influencing decreased levels of SOD and GPx enzymes, which are considered major defense mechanisms against ROS that may lead to the development of diabetes (type 2). Keywords: Melatonin, superoxide dismutase, glutathione peroxidase, oxidative stress, prediabetes Citation: Abd Ali ZA. Evaluation the levels of melatonin, glutathione peroxidase and superoxide dismutase enzymes in prediabetic individuals. Iraqi JMS. 2023; 21(1): 63-70. doi: 10.22578/IJMS.21.1.6